New Construction of Dakwah Tabligh Jamaah in Developing The Sprituality of Muslim People in Baja Dolok Village, Sipispis District, Serdang Bedagai District - Alif, Dimas; Nasution, Hasnah; Fitriani, Fitriani (International Journal of Nusantara Islam, 2024)
This research aims to explore the application of the Tablighi Jamaah’s da’wah in increasing the spirituality of Muslims in Baja Dolok Village, Sipispis District, Serdang Bedagai Regency. Using a qualitative descriptive approach, this research explores in depth social and religious phenomena related to preaching patterns and their influence on people’s spiritual lives. A sociology of religion approach is used to analyze the factors that influence the effectiveness of the Tablighi Jamaah’s da’wah in this region. Research data was collected through observation techniques and in-depth interviews with members of the Tablighi Jamaah, religious leaders and the local community. The research results show that the Tablighi Jamaah applies a unique da’wah approach, namely through the method of home visits (khuruj), religious discussions, and direct interactions in daily life. This approach has succeeded in increasing public awareness of the importance of practicing worship consistently and building a closer relationship with Allah. Apart from that, the Tablighi Jamaah’s preaching emphasizes real examples and the simplicity of living in accordance with Islamic teachings. The positive impact of this method can be seen in significant changes in the mindset and behavior of people who are more religious. However, this research also found challenges in implementing the Tablighi Jamaah’s da’wah, including negative assumptions from some communities, weak internal support in amar ma’ruf nahi munkar, as well as economic and geographical obstacles that influence the success of da’wah. However, the Tablighi Jamaah’s personal approach and consistency in preaching succeeded in overcoming most of these obstacles.